The Effectiveness Of Using Ice Breaking In Teaching Speaking At Students Of Junior High School - Suriyawan, Tasya; Yolanda, Alvina; Yassin, Muhammad (CV. Jendela Edukasi Indonesia, 2025)
This study aims to determine the effect of using ice breaking method on speaking skills of SMP Negeri 5 Pontianak students in English learning. The research design used is Dependent sample t-test, while the research method is quantitative with ice breaking method as the independent variable (X), while teaching speaking as the dependent variable (Y). The participants in this study were all 30 students of SMP Negeri 5 Pontianak, 16 female students and 14 male students, the data in the study were collected using an instrument (oral test), then normality test, homogeneity test and descriptive statistics were used to evaluate the requirements of data analysis. While the dependent t test analysis was used to test the hypothesis using computer software assistance through the SPSS (Statistcal Package For the Scial Sciens) version 22 for windows program. Based on the research findings and discussion, the following conclusions can be drawn: There is an effect of using ice breaking method on students' speaking skill at SMP Ngeri 5 Pontianak. This is indicated by the t-test result, which is t count (-9.421) > t table (1.699) with a significance level of 0.05. This shows that there is a positive effect of using ice breaking method on speaking skills in English learning, this means Ha is accepted and Ho is rejected.